2006
DOI: 10.1016/j.cub.2006.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor-Suppressor Gene fat Controls Tissue Growth Upstream of Expanded in the Hippo Signaling Pathway

Abstract: Together, these data suggest that Fat functions as a cell-surface receptor for the Expanded branch of the conserved Hippo growth control pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
268
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(287 citation statements)
references
References 44 publications
(70 reference statements)
14
268
0
3
Order By: Relevance
“…In addition, Pez may activate the Hippo pathway by binding to Kibra (Poernbacher et al, 2012). The Fat protocadherin, a cell surface molecule, was also identified as an upstream regulator of the Hippo pathway (Bennett and Harvey, 2006;Cho et al, 2006;Silva et al, 2006;Willecke et al, 2006;Tyler and Baker, 2007). Removing one copy of yki dramatically suppressed the fat mutant overgrowth phenotype (Bennett and Harvey, 2006;Silva et al, 2006;Willecke et al, 2006), indicating that yki is an important mediator of fat function.…”
Section: The Drosophila Hippo Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Pez may activate the Hippo pathway by binding to Kibra (Poernbacher et al, 2012). The Fat protocadherin, a cell surface molecule, was also identified as an upstream regulator of the Hippo pathway (Bennett and Harvey, 2006;Cho et al, 2006;Silva et al, 2006;Willecke et al, 2006;Tyler and Baker, 2007). Removing one copy of yki dramatically suppressed the fat mutant overgrowth phenotype (Bennett and Harvey, 2006;Silva et al, 2006;Willecke et al, 2006), indicating that yki is an important mediator of fat function.…”
Section: The Drosophila Hippo Pathwaymentioning
confidence: 99%
“…The Fat protocadherin, a cell surface molecule, was also identified as an upstream regulator of the Hippo pathway (Bennett and Harvey, 2006;Cho et al, 2006;Silva et al, 2006;Willecke et al, 2006;Tyler and Baker, 2007). Removing one copy of yki dramatically suppressed the fat mutant overgrowth phenotype (Bennett and Harvey, 2006;Silva et al, 2006;Willecke et al, 2006), indicating that yki is an important mediator of fat function. Fat activity is regulated by binding to another protocadherin, Dachsous (Ds) (Matakatsu and Blair, 2006), and is modulated by several proteins such as the casein kinase Discs overgrown (Dco) (Feng and Irvine, 2009;Sopko et al, 2009), the Golgi-resident kinase Four-jointed (Fj) (Rogulja et al, 2008;Willecke et al, 2008;Simon et al, 2010), and the Fat/Ds-interacting protein Lowfat (Lft) (Mao et al, 2009).…”
Section: The Drosophila Hippo Pathwaymentioning
confidence: 99%
“…The NF2 tumor suppressor, also known as Merlin (Mer), and Expanded (Ex), two ezrin/radixin/moesin (ERM) family actin-binding proteins (McClatchey and Giovannini 2005;Okada et al 2007), have been shown to positively regulate the Hippo pathway in Drosophila . Interestingly, genetic data indicate that Fat, a protocadherin tumor suppressor, also functions upstream of Hpo (Bennett and Harvey 2006;Cho et al 2006;Hariharan 2006;Silva et al 2006;Willecke et al 2006;Tyler and Baker 2007;Yin and Pan 2007). The fact that Fat may interact with another protocadherin, Dachsous, at the cell surface (Matakatsu and Blair 2004;Halbleib and Nelson 2006) suggests an exciting possibility that the Hippo pathway may be involved in cell growth regulation in response to cell-cell contact.…”
mentioning
confidence: 99%
“…Upon binding to Ds and subsequent phosphorylation by the kinase Disc Overgrown (Dco), Ft is thought to antagonize Wts degradation via the myosin Dachs. 25,26 Finally, the actin cytoskeleton has been reported to promote Yki activity (or that of its mammalian counterpart YAP -Yes-activated protein), representing a possible mechanical input into Hippo signaling. [27][28][29][30] Although some key molecular mechanisms that regulate Hippo signaling have been identified, many aspects of how these are modulated under physiological or stress conditions remain poorly explored.…”
mentioning
confidence: 99%